(untitled) (El-Wahat Journal for Research and Studies, 2025)
Numerous researchers in the realms of linguistics and literature have delved into the complexities of Structuralism. This theory, amalgamating both fields, marked the inception of a sustained effort to grapple with and delineate concepts like language, speech, and signs. Ferdinand de Saussure’s Semiology, functioning as an analytical tool, transcended disciplinary boundaries, leaving an indelible mark on fields ranging from philosophy and anthropology to psychology and literary theory.This article centers on Ferdinand de Saussure’s dichotomies and their profound impact on the works of narratologists, post-structuralists, and new historicists. The discussions sparked by structuralism were notably rich and creative, reshaping perspectives on language, text, authorship, history, and significant figures within these contexts. Consequently, deconstruction, post-modernism, and post-structuralism emerge as nuanced iterations, refining the foundational principles of structuralism. Keywords: Structuralism, Ferdinand de Saussure, Linguistics, Semiology, Significant figures, Literature, Jakobson, Foucault, dichotomy, authorship, text, deconstruction, post-modernism, new historicism, post-structuralism, narratology, literary theory, philosophy, psychology, disciplinary boundaries, language, dichotomies, history